Analisis Ketersediaan dan Kebutuhan Beras di Provinsi Bali Tahun 2020 - Suarni, Ni Wayan (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 10 No 1 (2022): Jurnal Manajemen AgribisnisDO - 10.24843/JMA.2022.v10.i01.p08, 2022)
Based on the BPS publication in 2020, Bali Province has the highest rice productivity in Indonesia at 58.49 Quintal per hectare (ha) in 2020 , but is not the largest rice producer in Indonesia. The total population of 4,317,404 people in 2020, this has resulted in large rice consumption in Bali. The purpose of this study was to analyze the availability and need for rice in the province of Bali. The method used in this research is literature study and secondary data analysis. The results of the analysis in this study indicate that Tabanan and Gianyar regencies are rice centers in Bali because they are supported by geographical conditions that can grow optimal rice commodities, in addition to the social conditions of the people who are more engaged in agriculture in rice commodities. This is evidenced by Tabanan Regency contributing 26.84% and Gianyar Regency 17.22% of the total rice production in Bali, including 2 districts with a surplus of rice namely Tabanan Regency and Gianyar Regency and 6 districts namely Badung, Jembrana, Buleleng, Bangli, Klungkung., Karangasem and 1 city of Denpasar with rice deficit.